Changes in education, wage inequality and working hours over time - Thomas Davoine; Jochen Mankart (Deutsche Bundesbank, 2017)
The US skill premium and college enrollment have increased substantially over the past few decades. In addition, while low-wage earners worked more than highwage earners in 1970, the opposite was true in 2000. We show that a parsimonious neoclassical model featuring skill-biased technical change, endogenous education and labor supply decisions can explain the change in the college education rate between 1967 and 2000 as well as the trend in the wage-hours correlation. Moreover, we show analytically and quantitatively that endogenous labor supply is important. Assuming constant hours significantly biases the estimates of the effects of skillbiased technological progress on college enrollment and the skill premium. Further, we find that limiting the maximum number of hours someone can work lowers welfare for almost all generations. Since it increases the skill premium, the welfare loss is most severe for the low-skilled, reaching almost one percent of life-time consumption.
Keywords: I24; J2; J31; 330; higher education; wage inequality; skill-biased technical change; labor supply; working time regulation